Depletion of ATP Limits Membrane Excitability of Skeletal Muscle by Increasing Both ClC1-Open Probability and Membrane Conductance - Leermakers, Pieter Arnold; Dybdahl, Kamilla Løhde Tordrup; Husted, Kristian Søborg; Riisager, Anders; de Paoli, Frank Vincenzo; Pinós, Tomàs; Vissing, John; Krag, Thomas Oliver Brøgger; Pedersen, Thomas Holm (Frontiers in Neurology, 2020)
Activation of skeletal muscle contractions require that action potentials can be excited and propagated along the muscle fibers. Recent studies have revealed that muscle fiber excitability is regulated during repeated firing of action potentials by cellular signaling systems that control the function of ion channel that determine the resting membrane conductance (Gm). In fast-twitch muscle, prolonged firing of action potentials triggers a marked increase in Gm, reducing muscle fiber excitability and causing action potential failure. Both ClC-1 and KATP ion channels contribute to this Gm rise, but the exact molecular regulation underlying their activation remains unclear. Studies in expression systems have revealed that ClC-1 is able to bind adenosine nucleotides, and that low adenosine nucleotide levels result in ClC-1 activation. In three series of experiments, this study aimed to explore whether ClC-1 is also regulated by adenosine nucleotides in native skeletal muscle fibers, and whether the adenosine nucleotide sensitivity of ClC-1 explains the rise in Gm muscle fibers during prolonged action potential firing. First, whole cell patch clamping of mouse muscle fibers demonstrated that ClC-1 activation shifted >30 mV in the hyperpolarized direction when clamping pipette solution contained 0 mM ATP compared with 5 mM ATP. Second, three-electrode Gm measurement during muscle fiber stimulation showed that glycolysis inhibition, with 2-deoxy-glucose or iodoacetate, resulted in an accelerated and rapid >400 % Gm rise during short periods of repeated action potential firing in both fast-twitch and slow-twitch rat, and in human muscle fibers. Moreover, ClC-1 inhibition with 9-anthracenecarboxylic acid resulted in either an absence or blunted Gm rise during action potential firing in human muscle fibers. Third, Gm measurement during repeated action potential firing in muscle fibers from a murine McArdle disease model showed that the rise in Gm was markedly accelerated in a subset of the fibers. Together, these results suggest that ClC-1 function is regulated by the level of adenosine nucleotides, and that the channel operates as a sensor of skeletal muscle metabolic state, limiting muscle excitability when energy status is low.